Comparison of three-view thoracic radiography and computed tomography for detection of pulmonary nodules in dogs with neoplasia - Armbrust, Laura J.; Biller, David S.; Bamford, Aubrey; Chun, Ruthanne; Garrett, Laura D.; Sanderson, Michael W. (My University, 2012)
Objective — To compare the detection of pulmonary nodules by use of 3-view thoracic radiography and CT in dogs with confirmed neoplasia. Design — Prospective case series. Animals — 33 dogs of various breeds. Procedures — 3 interpreters independently evaluated 3-view thoracic radiography images. The location and size of pulmonary nodules were recorded. Computed tomographic scans of the thorax were obtained and evaluated by a single interpreter. The location, size, margin, internal architecture, and density of pulmonary nodules were recorded. Sensitivity, specificity, positive predictive value, and negative predictive value were calculated for thoracic radiography (with CT as the gold standard). Results — 21 of 33 (64%) dogs had pulmonary nodules or masses detected on CT. Of the dogs that had positive CT findings, 17 of 21 (81 %) had pulmonary nodules or masses detected on radiographs by at least 1 interpreter. Sensitivity of radiography ranged from 71 % to 95%, and specificity ranged from 67% to 92%. Radiography had a positive predictive value of 83% to 94% and a negative predictive value of 65% to 89%. The 4 dogs that were negative for nodules on thoracic radiography but positive on CT were all large-breed to giant-breed dogs with osteosarcoma. Conclusions and Clinical Relevance — CT was more sensitive than radiography for detection of pulmonary nodules. This was particularly evident in large-breed to giant-breed dogs. Thoracic CT is recommended in large-breed to giant-breed dogs with osteosarcoma if the detection of pulmonary nodules will change treatment.
Keywords: Pulmonary metastatic disease; Three-view thoracic radiography; Computed tomography; Neoplasia; Dogs